Pengembangan Media Pembelajaran E-Magazine Berbasis Pendekatan Saintifik Pada Pembelajaran IPA Materi Sifat-Sifat Cahaya Kelas IV SD - Nur Alfiah, Putri; Edwita, Edwita; Supriatna, A. R. (Universitas Nusantara PGRI Kediri, 2022)
This study aims to produce e-magazine learning media based on a scientific approach for science learning material properties of light for 4th-grade elementary school. The development of this e-magazine uses the Research dan Development method based on the ADDIE model. The subjects of this study were 4th-grade students at SDN Rawamangun 12 Pagi. Data collection techniques were carried out by observation, interviews, questionnaires and pre-test and post-test. The study's results based on expert validation questionnaires showed the feasibility of e-magazines from media, material and linguists experts with percentage gains of 96, 42%,82,50 % and 95% in the excellent category. The results of product trials in the one-to-one and small group evaluation showed this product obtained a percentage of 83,56% and 95,72% in the outstanding category. Implementation in learning increased the average score of students from 80 (pre-test) to 92 (post-test), and the average student assessment of the e-magazine obtained a percentage of 92% in the excellent category. Based on these results, it can be concluded that the e-magazine learning media based on a scientific approach is suitable for use in the 4th grade of the elementary school in the science of the properties of light.